The Treatment of Giant Cell Arteritis in Different Clinical Settings - Pfeil, Alexander; Oelzner, Peter; Hellmann, Peter (Frontiers in Immunology, 2019)
This paper aims to raise awareness of the different disease courses, comorbidities, and therapy situations in patients with giant cell arteritis (GCA), which require a differentiated approach and often a deviation from current treatment guidelines. With the approval of tocilizumab (TOC), which specifically binds to both soluble and membrane-bound IL-6 receptor and inhibits IL-6 receptor-mediated signalling, the spectrum of available effective treatment options has been significantly broadened. TOC yields an extensive range of possible applications that go beyond a glucocorticoid-saving effect. In this context, the treatment of GCA is dependent on the disease course as well as the associated comorbidities. The different stages of GCA in association to co-morbidities require an detailed treatment strategy.